A Bionic Self-Assembly Hydrogel Constructed by Peptides With Favorable Biosecurity, Rapid Hemostasis and Antibacterial Property for Wound Healing - Wang, Yang; Li, Xiao; Yuan, Juzheng; Wang, Xudan; Tao, Kaishan; Yan, Jin (Frontiers in Bioengineering and Biotechnology, 2022)
Bionic self-assembly hydrogel derived by peptide as an effective biomedical hemostatic agent has always gained great attention. However, developing hydrogels with eminent-biosecurity, rapidly hemostatic and bactericidal function remains a critical challenge. Hence, we designed an injectable hydrogel with hemostatic and bactericidal function based on Bionic Self-Assembling Peptide (BSAP) in this study. BSAP was formed with two functionalized peptides containing (RADA)4 motif and possessed the ability to self-assemble into nanofibers. As expected, BSAP could rapidly co-assemble into hydrogel network structure in situ driven by Ca2+. The hydrogel with a concentration of 5% showed a superior microporous structure and excellent shear thinning characteristics, as well as injectability. Moreover, in the foot trauma model and tail amputation model, the fabricated hydrogel exhibited a lower blood clotting index and dramatically reduced blood clotting time and bleeding volume. Remarkably, the hydrogel reduced inflammatory responses by blocking bacterial infection, promoting wound healing. Finally, the hydrogel is highly hemocompatible and has no cytotoxicity. Overall, this work provides a strategy for developing a high-biosecurity hydrogel with hemostatic and antibacterial properties, which will allow for the clinical application of BSAP.